FORMINGOF INTERCULTURAL COMPETENCE OF STUDENTS: REALITIES AND CHALLENGES OF THE MODERNEDUCATIONAL ENVIRONMENT (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The social and economic changes taking place in our society determine the requirements for the quality of the training of students with higher professional education, putting forward new tasks for the modern methodological science. These requirements can not impose a reflection on certain issues of the theory of teaching a foreign language, when the priority is the teaching of intercultural interaction, that is, in this case, it is not just about mastering a foreign language, but above all – all types of competencies, in particular intercultural competence.The purpose of the article is to analyze the concept of 'intercultural competence' from the point of intercultural interaction, the use of linguistic material, taking into account the national specification of the participants in the language dialogue. It seems that teaching students to communicate both orally and in writing, to reproduce, and not just understand the language already created by someone, is a difficult task, more complicated by the fact that communication is not just a verbal process. Its effectiveness depends on many factors: knowledge of language, conditions and culture of communication, rules of etiquette; knowledge of non-verbal forms of expression (facial expressions, gestures), deep background knowledge, etc. Today, there is a sufficiently elaborate classification of competencies, which is the basis of the communication process and ensures its success. Modern researchers distinguish a number of competencies that reach the ultimate goal of learning – the formation of communicative competence. As part of the communicative competence that the student must necessarily possess, we consider intercultural competence as a student's activity associated with communication in the international situations, and this communication always involves conflicts between knowledge and ignorance, even in the context of communication in one language. We believe that in the process of forming the intercultural competence of the student, the teacher should familiarize him with the national-cultural features of the behavior of foreigners, such as the use of certain facial expressions and gestures, in order to avoid possible conflicts in interethnic communication.Thus, using theoretical empirical general scientific methods in the study of the question of the formation of intercultural competence, one can conclude that the formation of intercultural competence involves mastering the following skills: to see from representatives of other cultures not only that which distinguishes us, but also that which unites; change attitudes as a result of understanding another culture; abandon stereotypes; use knowledge of another culture for a deeper knowledge of one's own. Intercultural competence is formed in the process of learning foreign language communication, taking into account the cultural and mental differences of language carriers and is a prerequisite for a successful dialogue of cultures. Awareness of possible problems arising in the intercultural communication of representatives of different cultures, understanding of values and generally accepted norms of behavior are very significant factors in the studying of a foreign language.
Keywords: communicative competence, intercultural competence, intercultural communication, language, correctness, tolerance, interaction.